Obtention and characterization of dried gels prepared with whey proteins, honey and hydrocolloids mixture - Rodríguez, Ana C. (2017)
BACKGROUND: Large amounts of honey and liquid whey derived from the dairy industry are produced in Argentina. Honeyis exported in bulk and whey is transformed into whey protein concentrates and isolates. The objective of this work was toinvestigate the effect of pH, composition and storage time on the properties of dried gels with honey, whey proteins andhydrocolloids.RESULTS: Color properties varied according to pH and composition. The fracture stress of dried gels prepared with corn starchwas higher than that of gels prepared with guar gum in all conditions assayed. Young’s modulus was higher at pH 7 for bothcompositions and increased with storage time. Rubbery characteristics were found in dried gels with guar gum, while both cornstarch and guar gum made the microstructure rougher. Multivariate analysis showed that samples could be grouped by pH.Panelists preferred pH 7 products over acidic ones, and no significant differences in sensory properties were found using eithercorn starch or guar gum in the formulation.CONCLUSION: The results demonstrated that it is possible to generate a new product, which may open new applications forhoney and whey in food formulations.